Study on the characteristics of municipal solid waste from Perlis disposal site - Rohada Binti Saad (School of Environmental Engineering University Malaysia Perlis, 2011)
Increasing population levels, rapid economic growth and rise in community living standard accelerates the generation rate of municipal solid waste (MSW) in Perlis. The objectives of this study are to determine parameters density, pH, moisture content, calorific value (CV) and heavy metal (Nickel, Zinc, Manganese and Ferum ). Four sample were obtained for this study. The samples were collected at the Perlis dumping siteand analyzed at the laboratory to determined the characteristic of MSW. From the study, the three main constitutions of the waste generated were food, paper and cardboard and plastic.